A Survey on Advanced Methods for Segmentation of Structures in H & E Stained Images - Pawar, SB; Gaikwad, V (International Journal of Computer Sciences and Engineering, 2025)
Segmenting a broad class of histological structures is a necessary to identify the presence of cancer, to clarify spatial relation between histological structures in the tumor environments, making precise medicine studies easy, and provide an exploratory tool for pathologists. Histological structure determination helps explain spatial tumor biology and adds an advantage for health care organizations. Role focuses on the segmentation of histological structures present in colored images with stains (H & E) of the breast tissue. Accurate segmentation of histological structures can help build a spatial interaction map identifying the relations between the pixels to serve as an exploratory tool for pathologists. Graph theory based methods proposed based on spatial color statistics and neighborhood of nuclei statistics as well as designed a new region-based score for evaluating segmentation algorithms. In the first method, pair wise pixel color statistics measures in an H&E optimized color space built to enhance the separation between hematoxylin and eosin stains. The first method is expected to be successful in segmenting structures with well-defined boundaries (e.g., adipose tissues, blood vessels).The second method is designed to segment large amorphous histological structures (e.g., tumor nests), the spatial statistics of inter-nuclei distances is considered. Working with expertly annotated breast H&E images, this paper demonstrated the ability of proposed algorithms to identify significant histological structures, and thus enable the understanding of their spatial relationships, and perhaps infer the status of the disease.